Current view of neoadjuvant chemotherapy in primarily resectable pancreatic adenocarcinoma - Eid, Michal; Ostřížková, Lenka; Kunovský, Lumír; Brančíková, Dagmar; Kala, Zdeněk; Hlavsa, Jan; Janeček, Pavel; Kosíková, Ivana; Blažková, Monika; Slabý, Ondřej; Mayer, Jiří (Neoplasma, 2021)
Pancreatic ductal adenocarcinoma (PDAC) is now the 11th most common cancer and in 2018 there were 458,918 new cases worldwide. In the Czech Republic, a total of 2,173 patients were diagnosed in 2015, ranking the second in incidence worldwide. In contrast to other malignancies, recent research has not brought any major breakthrough in the treatment of PDAC and hence the prognosis remains very serious. Radical resection is the only curative approach, but after the initiation of the standard pathological evaluation of the resected tissue, according to the Leeds protocol, 80% of the resections are R1 (resections with microscopically positive margins). The results of studies in patients with borderline resectable or locally advanced PDAC prefer neoadjuvant chemotherapy or chemoradiotherapy. This approach leads to a higher number of radical R0 resections and better survival. For neoadjuvant treatment in patients with primarily resectable PDAC, most results come from retrospective analysis or phase II trials. However, recently, data from three randomized clinical trials with neoadjuvant therapy for resectable PDAC were presented. These results support the use of chemotherapy or chemoradiotherapy prior to surgery. In the trials published to date, there are differences in chemotherapeutic regimens, cytostatic doses, and the definition of resectability. Thus, up-front resection with adjuvant chemotherapy is still the standard of care and a well-designed randomized trial using neoadjuvant therapy is now necessary.
Keywords: protokoly protinádorové kombinované chemoterapie; retrospektivní studie; lidé; Humans; neoadjuvantní terapie; Carcinoma, Pancreatic Ductal; Randomized Controlled Trials as Topic; nádory slinivky břišní; randomizované kontrolované studie jako téma; Antineoplastic Combined Chemotherapy Protocols; Neoadjuvant Therapy; duktální karcinom slinivky břišní; Retrospective Studies; Pancreatic Neoplasms